A case-control study of acute appendicitis and diet in children. Issue 4 (December 1986) - Nelson, M; Morris, J; Barker, D J; Simmonds, S
Abstract : The diets of 53 Southampton children who had had appendicitis were compared with those of two sets of age-sex matched controls using a seven-day weighed food record. One set of controls comprised classmates of the cases; the other was a random sample of all schoolchildren in the city. The cases weighed less and were shorter in height; they had lower intakes of energy, all the main nutrients and water. The differences in weight and water intake were statistically significant. Low water intake was identified as a risk factor independent of other factors. Consumption of dietary fibre from cereals and vegetables in relation to total energy intake and body weight was similar in cases and controls.